Effects of COVID‐19 on Parkinson's Disease Clinical Features: A Community‐Based Case‐Control Study. Issue 8 (11th June 2020) - Cilia, Roberto; Bonvegna, Salvatore; Straccia, Giulia; Andreasi, Nico Golfrè; Elia, Antonio E.; Romito, Luigi M.; Devigili, Grazia; Cereda, Emanuele; Eleopra, Roberto
Abstract: The impact of coronavirus disease 2019 (COVID‐19) on clinical features of Parkinson's disease (PD) has been poorly characterized so far. Of 141 PD patients resident in Lombardy, we found 12 COVID‐19 cases (8.5%), whose mean age and disease duration (65.5 and 6.3 years, respectively) were similar to controls. Changes in clinical features in the period January 2020 to April 2020 were compared with those of 36 PD controls matched for sex, age, and disease duration using the clinical impression of severity index for PD, the Movement Disorders Society Unified PD Rating Scale Parts II and IV, and the nonmotor symptoms scale. Motor and nonmotor symptoms significantly worsened in the COVID‐19 group, requiring therapy adjustment in one third of cases. Clinical deterioration was explained by both infection‐related mechanisms and impaired pharmacokinetics of dopaminergic therapy. Urinary issues and fatigue were the most prominent nonmotor issues. Cognitive functions were marginally involved, whereas none experienced autonomic failure. © 2020 International Parkinson and Movement Disorder Society